Clinical characteristics of acute kidney injury associated with tropical acute febrile illness - Omar, FD; Phumratanaprapin, W; Silachamroon, U; Hanboonkunupakarn, B; Sriboonvorakul, N; Thaipadungpanit, J; Pan-Ngum, W (MDPI, 2023)
Tropical acute febrile illness (TAFI) is one of the most frequent causes of acute kidney injury (AKI). The prevalence of AKI varies worldwide because there are limited reports available and different definitions are used. This retrospective study aimed to determine the prevalence, clinical characteristics, and outcomes of AKI associated with TAFI among patients. Patients with TAFI were classified into non-AKI and AKI cases based on the Kidney Disease Improving Global Outcomes (KDIGO) criteria. Of 1019 patients with TAFI, 69 cases were classified as having AKI, a prevalence of 6.8%. Signs, symptoms, and laboratory results were significantly abnormal in the AKI group, including high-grade fever, dyspnea, leukocytosis, severe transaminitis, hypoalbuminemia, metabolic acidosis, and proteinuria. 20.3% of AKI cases required dialysis and 18.8% received inotropic drugs. Seven patients died, all of which were in the AKI group. Risk factors for TAFI-associated AKI were being male (adjusted odds ratio (AOR) 3.1; 95% CI 1.3-7.4), respiratory failure (AOR 4.6 95% CI 1.5-14.1), hyperbilirubinemia (AOR 2.4; 95% CI 1.1-4.9), and obesity (AOR 2.9; 95% CI 1.4-6). We recommend clinicians investigate kidney function in patients with TAFI who have these risk factors to detect AKI in its early stages and offer appropriate management.